1996
DOI: 10.1128/iai.64.9.3491-3496.1996
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of a cell proliferation-inhibiting protein produced by Helicobacter pylori

Abstract: Despite the induction of an immunological reaction, Helicobacter pylori-associated gastritis is a chronic disease, suggesting that this microbe can evade the host immune defense. Previous studies by our group showed that H. pylori suppresses the in vitro proliferative response of human mononuclear cells to mitogens and antigens. Here we demonstrate that the antiproliferative activity of H. pylori also affects the proliferation of various mammalian cell lines (U937, Jurkat, AGS, Kato-3, HEP-2, and P388D1). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 43 publications
1
28
1
Order By: Relevance
“…At variance with our findings, previous studies have suggested that H. pylori-infected individuals have down-regulated H. pylorispecific T cell responses in the circulation compared with healthy individuals [24,34,35]. However, the antigens used in those studies were inactivated whole bacteria or whole cell lysates, of which at least the latter have been shown to contain immunomodulating substances [36]. The different antigen preparations used in previous and in our study may explain the differences between the results obtained, since we used purified or recombinant antigens in addition to the MP preparation and since all our antigen preparations were devoid of LPS activity.…”
Section: Discussioncontrasting
confidence: 98%
“…At variance with our findings, previous studies have suggested that H. pylori-infected individuals have down-regulated H. pylorispecific T cell responses in the circulation compared with healthy individuals [24,34,35]. However, the antigens used in those studies were inactivated whole bacteria or whole cell lysates, of which at least the latter have been shown to contain immunomodulating substances [36]. The different antigen preparations used in previous and in our study may explain the differences between the results obtained, since we used purified or recombinant antigens in addition to the MP preparation and since all our antigen preparations were devoid of LPS activity.…”
Section: Discussioncontrasting
confidence: 98%
“…Inhibition of gastric epithelial cells by H. pylori in vitro has been reported by several investigators. [6][7][8][9][10]25 Ricci et al 8 and Chang et al 9 reported that VacA but not CagA protein inhibits growth and proliferation of gastric epithelial cells. On the other hand, Knipp et al demonstrated using isogenic knockout mutant strains that the antiproliferative agent of a soluble H. pylori extract is a protein with an apparent native molecular mass of 100 kDa, and that urease enzyme, the cagA gene product, or the vacuolizing cytotoxin of H. pylori are not responsible for this inhibitory action.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Knipp et al demonstrated using isogenic knockout mutant strains that the antiproliferative agent of a soluble H. pylori extract is a protein with an apparent native molecular mass of 100 kDa, and that urease enzyme, the cagA gene product, or the vacuolizing cytotoxin of H. pylori are not responsible for this inhibitory action. 25 Wagner et al showed that viable H. pylori, regardless of cagA and VacA expression or their extracts, inhibits the growth of gastric cells through inhibition of DNA synthesis as well as through induction of apoptosis of gastric cells. 6 These reports suggest that H. pylori inhibits gastric cell proliferation through VacA-dependent and -independent mechanisms, and furthermore, that the latter process seems to be correlated with the protein demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on cell migration is dependent on a low (< 12 kDa) molecular mass component and seems not to be mediated by VacA or CagA (Ricci et al, 1996). The inhibition of cell proliferation is dependent on different bacterial virulence factors, one of which has been identi®ed as the VacA cytotoxin (Ricci et al, 1996), the other two being low (< 12 kDa) (Ricci et al, 1996) and high (100 kDa) (Knipp et al, 1996), as yet unidenti®ed, molecular mass components. Also, it has been shown that H. pylori-dependent inhibition of cell proliferation is associated with the induction of apoptosis of cultured mucosal cells, thus suggesting a direct link between the two phenomena (Wagner et al, 1997).…”
Section: Mechanisms Of H Pylori-induced Cell Damagementioning
confidence: 99%
“…H. pylori, in addition to causing gastric mucosal cell damage, also impairs the processes of cell migration and proliferation in cultured gastric mucosal cells in vitro (Knipp et al, 1996;Ricci et al, 1996;Wagner et al, 1997). The effect on cell migration is dependent on a low (< 12 kDa) molecular mass component and seems not to be mediated by VacA or CagA (Ricci et al, 1996).…”
Section: Mechanisms Of H Pylori-induced Cell Damagementioning
confidence: 99%